2022
DOI: 10.15537/smj.2022.43.6.20220090
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to routine checkups use among Saudis from the perspective of primary care providers

Abstract: Objectives: To explore the perspectives of primary care providers (PCPs) on the low use of and barriers to routine checkups among Saudi adults. Methods:A qualitative phenomenological study design was used. Interviews were carried out between (December 2020 and February 2021) with 19 PCPs working at 5 primary healthcare centers (PHCs) operated by the Ministry of Health (MOH) in Makkah, Saudi Arabia. Descriptive statistics were performed to characterize participants, and a directed content analysis was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…Furthermore, healthcare system-related barriers were reported by Alzahrani et al, such as limited staffing, crowded healthcare centers, and shortage of required infrastructure to perform routine checkups. 24 Comparing our study to similar international investigations revealed several similarities as well as differences. Eke et al conducted a study in southeastern Nigeria to evaluate the perception and practice of periodic medical checkups by traders.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, healthcare system-related barriers were reported by Alzahrani et al, such as limited staffing, crowded healthcare centers, and shortage of required infrastructure to perform routine checkups. 24 Comparing our study to similar international investigations revealed several similarities as well as differences. Eke et al conducted a study in southeastern Nigeria to evaluate the perception and practice of periodic medical checkups by traders.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, healthcare system-related barriers were reported by Alzahrani et al, such as limited staffing, crowded healthcare centers, and shortage of required infrastructure to perform routine checkups. 24 …”
Section: Discussionmentioning
confidence: 99%
“…The third influential factor identified in our study was knowledge about PHE. This result is consistent with previous research (22)(23)(24) and highlights the importance of informed decision-making in healthcare utilization. It is worth noting that knowledge about PHE is intertwined with other factors such as educational level and occupation.…”
Section: Discussionsupporting
confidence: 93%
“…(18) The high level of awareness among the attendants was unbalanced by the low frequency of uptake of routine checkup, as only one third of them or one of their family members undergone routine checkup, similar findings was reported before in Saudi Arabia, (19) that had been attributed partly to the provider-related and health system-related factors such as crowdness and busy staff of the primary health care centers. (20) The level of awareness about the routine screening investigation was found to increase significantly with higher education level, it is expected that the "educated individuals are more likely to understand the importance of preventive services and take action to protect their health before they face sickness". ( 21) Almost two thirds of the respondents were females, which indicates that they are the most likely to use the primary health care services preventive, either for themselves or for their children, the same was found in previous researches (22,23).…”
Section: Discussionmentioning
confidence: 99%